Sexual/Textual Politics in the Women of Ophelia A. Dimalanta’s Poems - Perez, Ma. Socorro Q (Archīum Ateneo, 2017)
The study attempts to show that while Ophelia A. Dimalanta’s excellent New Critical training and education have rendered her a quintessential poet conscious of form, technique, and craftsmanship, which in turn, has been foregrounded by her equally New Critical-trained colleagues, this New Critical tradition has limited the study of her oeuvre to artistic structure and form, glossing over myriad concerns that the poems may have. The present study, in turn, has recuperated form, technique, and genre to encode the feminism that undergirds her poetic vision. Foregrounding Dimalanta’s vision enfleshed in art, the study recuperates the sexual/textual politics in Dimalanta’s Lady Polyester: Poems Past and Present from the lens of Toril Moi